Efektifitas Penggunaan Cold Pack dibandingkan Relaksasi Nafas Dalam untuk Mengatasi Nyeri Pasca Open Reduction Internal Fixation (ORIF) - Agung Kristanto; Fitri Arofiati (Universitas Muhammadiyah Yogyakarta, 2016)
Background: Pain is the main problem of patients post surgery. The reguler pain management are use pharmacological and non pharmacological therapy. One of the variety of non pharmacology therapy is cold compression, which is an innovation of cold pack. Aim of Research The purpose of this study was to compare the effectiveness of cold compress cold pack with deep breathing relaxation in reducing pain for patients with post ORIF (Open Reduction Internal Fixation). Research Methods: This study design was Quasi-Experiments pre-Test Post-Test With Control Group. There were patients post ORIF in the third class ward dr Soeradji Tirtonegoro Klaten consisting of 15 patients in the intervention cold compress with cold pack and 15 patients the control group in the deep breathing relaxation as respondents. The treatment was done 4 times post analgetic I and post analgetic II. Pain level was measured by VAS pain scale and conducted in 2 times the first after analgesic 1, second measurement after analgesic 2. The statistical test for analysis data used independent test t-test and paired t- test.Result: The results of independent t-test before the intervention is relatively the same. Meanwhile, after intervention the level of pain from intervention group which was cold pack decreased 3 (three) point and from control group (deep breathing relaxation) decreased 1 (one) point. The statictical analysis measurement showed that p value was 0,00.Conclusion: It is proved that the intervention of cold pack has more effective than deep breathing relaxation. Suggestion: Used cold pack further enhanced as one implementation of independent nursing, but still pays attention to changes in the patient's physical condition.